Meningkatkan Hasil Aktivitas Belajar dengan Menggunakan Pendekatan Emotional Activities Learning dalam Pembelajaran Ilmu Pengetahuan Alam - Suharno (IBTIDA', 2023)
This research aims to determine the increase in learning activities of Emotional Activities Learning (learning that develops students' interest and attention) of Class IX-A students at SMP Negeri 1 Sekaran, Lamongan Regency. The approach used in this study is a qualitative approach. The type of research used is classroom action research (PTK). The research was designed in the form of an action cycle. The action cycle consists of four activities, namely action planning, implementation, observation, and reflection. The research was carried out in three cycles. In this research, the instruments used include observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, drawing conclusions, or verification. In cycle I the average value obtained was 66.91%. In Cycle II, 18 students got a score above 65. This means that the learning cycle score was 68.51%. In Cycle III the average score obtained was 82.06%. So in this research activity, there is no need to carry out research activities in the next cycle. So that this research activity can be declared successful or complete.